Case 3759: Conservation of Costaclymenia Schindewolf, 1920 and Costaclymeniidae Ruzhencev, 1957 by proposed designation of a neotype for Goniatites binodosus Münster, 1832 (Mollusca, Cephalopoda, Ammonoidea) - Korn, Dieter; Price, John D; Weyer, Dieter (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application, under Article 75.6 of the Code, is to conserve the current usage and concepts of the Late Devonian genus Costaclymenia Schindewolf, 1920 and the family Costaclymeniidae Ruzhencev, 1957, by setting aside all previous types and to designate as a neotype for Goniatites binodosus Münster, 1832, a specimen from the type locality. Costaclymenia Schindewolf, 1920 is a widely used genus name, but the type species Goniatites binodosus Münster, 1832 is known almost entirely from secondary material. The fragmentary holotype has not been referred to since the original description and is probably lost. Without a neotype for the species binodosus, the genus Costaclymenia and the family Costaclymeniidae would all be problematic taxa.
Keywords: Nomenclature; taxonomy; Ammonoidea; Clymeniida; Münster; Devonian; ammonoids